Analysing Signal Strength and Connection Speed in Cloud Networks for Enterprise Business Intelligence - Gananda Hayardisi; Kudang Boro Seminar; Arief Ramadhan (Universitas Ahmad Dahlan, 2018)
Signal strength and speed connection data which are collected and available in a company have not been optimally and beneficially processed and stored for more added value business purposes. Therefore, the collected data need to be utilized in more strategic way for business intelligent in the company that enables management to conduct better and smarter decision making. This research is aimed to develop a business intelligence system based on cloud computing platform which is more flexible and manageable in terms of cost and resources. The developed system adopts the three tier architectures of data warehouse that provides data extraction, transform, and load (ETL) functions and the creation of dimensional models and visualization in dashboard forms. Business intelligence solutions have been created based on cloud computing using Microsoft Azure SQL Database as database storage of data warehouse and Power BI as a dimensional model and dashboard visualization. The developed system prototype has been implemented and tested for its functionalities and capabilities in a web platform.